Literature review: transforming human resource management functions from administrative to strategic business partner - literature meta-analysis 2015-2024 - Nugroho, Ageng; Wulandhari, Otti; Sudrajat, Enjat; Masitoh, Masitoh (Enrichment : Journal of Management, 2025)
The evolution of the human resource management function from administrative roles to strategic business partners has become a major focus in the era of digitalization and economic globalization. It aims to analyze the comprehensive characteristics and transformation patterns of human resource functions through a systematic meta-analysis approach to the academic literature for the period 2015-2024. The research methodology adopts a qualitative meta-synthesis approach with article selection criteria including peer-reviewed publications, temporal range 2015-2024, focus on transformation of strategic HR roles, accessibility of accredited academic databases, and high thematic relevance. The analytical approach uses structured thematic synthesis techniques and systematic content analysis of ten relevant articles from internationally reputable scientific repositories. The results of the study identified three phases of progressive transformation including the transition stage, the development of strategic capabilities, and the maturity of business partnerships. Determinants of transformation success include executive management commitment, sustainable digital competency development, adaptive organizational culture, and external competitive pressures. Transformation has a significant positive impact on operational efficiency, organizational productivity, employee engagement, and the company's innovation capacity. The era of digitalization has become a fundamental catalyst for changing the paradigm of HR from an administrative mindset to a strategic orientation with an emphasis on technology-based decision-making and data analytics.